2009
DOI: 10.1073/pnas.0901414106
|View full text |Cite
|
Sign up to set email alerts
|

Basic mechanism for abrupt monsoon transitions

Abstract: Monsoon systems influence the livelihood of hundreds of millions of people. During the Holocene and last glacial period, rainfall in India and China has undergone strong and abrupt changes. Though details of monsoon circulations are complicated, observations reveal a defining moisture-advection feedback that dominates the seasonal heat balance and might act as an internal amplifier, leading to abrupt changes in response to relatively weak external perturbations. Here we present a minimal conceptual model captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
129
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(141 citation statements)
references
References 44 publications
10
129
2
Order By: Relevance
“…Similarly, the Hadley Centre models (HadGEM2-CC and HadGEM2-ES) and the Institute Pierre Simon Laplace models (IPSL-CM5A-LR and IPSL-CM5A-MR) capture very little rainfall over the all-India region with comparatively higher rainfall over the Himalayan mountains and the Bay of Bengal. As discussed by Levermann et al (2009), the monsoon region can enter a climatic regime in which latent heat transport towards land is insufficient to sustain a monsoon circulation, which may lead to abrupt monsoon transition (Zickfeld et al, 2005) as observed in the past Cook et al, 2010;Sinha et al, 2011). While observations clearly show that the ISM is currently within the active monsoon regime, it is possible that the CMIP-5 models that exhibit a very weak ISM are outside this regime.…”
Section: Model Evaluationmentioning
confidence: 86%
“…Similarly, the Hadley Centre models (HadGEM2-CC and HadGEM2-ES) and the Institute Pierre Simon Laplace models (IPSL-CM5A-LR and IPSL-CM5A-MR) capture very little rainfall over the all-India region with comparatively higher rainfall over the Himalayan mountains and the Bay of Bengal. As discussed by Levermann et al (2009), the monsoon region can enter a climatic regime in which latent heat transport towards land is insufficient to sustain a monsoon circulation, which may lead to abrupt monsoon transition (Zickfeld et al, 2005) as observed in the past Cook et al, 2010;Sinha et al, 2011). While observations clearly show that the ISM is currently within the active monsoon regime, it is possible that the CMIP-5 models that exhibit a very weak ISM are outside this regime.…”
Section: Model Evaluationmentioning
confidence: 86%
“…They may dominate the seasonal heat balance on long timescales, and explain abrupt changes in monsoon rainfall under small changes in external forcing [21]. In the conceptual model of Levermann et al [21], higher summer temperatures increase the seasonal landsea thermal contrast due to the different heat capacity of land and ocean, strengthening the monsoon onset circulation and allowing for more precipitation. Weaknesses in the simulation of these seasonal processes may explain the lack of positive feedbacks between temperature and rainfall changes on long timescales.…”
Section: Potential Reasons For the Mismatch On Climatementioning
confidence: 99%
“…5 is manifest most strongly as contrasting precipitation responses in the wet and dry regions of the tropics (e.g., Chou et al 2007;Allan et al 2010). An alternative perspective is to again consider the energy balance: latent heating through condensation of water droplets and eventual precipitation must be balanced by cooling through radiative processes and dry static energy transport, assuming other terms such as sensible heating are small (Muller and O'Gorman 2011); this may also have bearing upon the viability and stability of monsoon systems (Levermann et al 2009). …”
Section: The Atmospheric Hydrological Cyclementioning
confidence: 99%